До анатомії плоду видів роду Pastinaca L. - Palamarchuk, E.P.; Vakulenko, T.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
As a result of the comparative anatomic analysis of fruit of six species of genus Pastinaca L. the most important and constant features were chosen, which can be used for diagnostics of species, and for identification of vegetative raw material.